The Implementation Of SQ3R Strategy To Teach Reading News Item Text To Tenth Grade Students Of Senior High School - SURYA DHARMA, AHMAD (RETAIN : Journal of Research in English Language Teaching, 2013)
English has been the language of the world. Many countries in this world have used English as their first or second languae. In our country, Indonesia, English is now considered as the second language. We can see advertisements or shows using not only Bahasa Indonesia but also English as well. In order to be able to use English well, there are four skills we need to master, they are: reading, writing, listening and speaking skill. For the students, reading skill considered as the most difficult skill to handle. Because in reading, students not only have to read a text carefully and thoroughly but also they need to comprehend the content. Comprehending the content of a text is not an easy job, it needs plan or strategy. Reading strategy is very important to help students comprehending text so that they not only read a text but also understand about the content. There are so many reading strategies available to be used, one of them are SQ3R. SQ3R is a useful strategy to read articles, book, tabloid chapter, nonfiction text, etc. This strategy will motivate the students to focus and concentrate on the text with its 5 different phase. SQ3R strategy has 5 phases. Every phases has different role and activities to support the students in comprehending the content of the text. In survey phase, the students pre-read the primary source text by skimming headings, sub-headings, title, pictures, caption, bold faced type, concluding paragraphs, charts and key vocabulary. In addition, students should make prediction from this phase. The second phase is question. The students are asked to create questions related to the content of the text (turn headings and/or sub-headings into questions). Later they will have to answer the questions. In read phase, the students are asked to read the text carefully to find details and main idea of the text. In recite phase, students are asked to answer their questions and also asked to orally retell the text with their own words. The last step is review. In this phase, the students once again are asked to review the text to strengthen their understanding about the text. They are also asked to summarize the text to remember the informations from the text. Using news item text in this learning process is appropriate because news item text is one of nonfiction text and it also learnt in the tenth grade of senior high school students. This study is a descriptive qualitative research and this research aims to describe the use of SQ3R as a strategy in teaching reading news item text, the students reading comprehension after using SQ3R and also students’ responses toward the strategy. For the research instrument, the researcher uses observation checklist with the help of field notes, students’ task and also questionnaire. The data obtained in this research will be served in the form of sentences. After the observation, the researcher found that SQ3R was really helpful for the students to comprehend the text and also increased their reading ability. The result of the students’ tasks indicated that the students’ reading comprehension increased. The students also agreed that by using SQ3R in learning reading was very useful in the classroom. The researcher would like to suggest English teacher to use SQ3R as an alternative strategy in teaching reading. It is important because reading comprehension is essential and this strategy could help students to achieve it. Key Words: SQ3R (Survey, Question, Read, Recite, Review), strategy, teaching reading, news item text. Abstrak Bahasa Inggris telah menjadi bahasa yang mendunia. Banyak negara telah menggunakan bahasa Inggris sebagai bahasa pertama ataupun kedua. Di negara kita, Indonesia, bahasa Inggris telah dianggap menjadi bahasa kedua. Kita bisa melihat banyak iklan yang tak hanya menggunakan bahasa Indonesia namun juga menggunakan bahasa Inggris. Untuk dapat menggunakan bahasa Inggris dengan benar, ada 4 (empat) kemampuan dasar yang harus dikuasai, yaitu: membaca, menulis, mendengar dan berbicara. Untuk para siswa, kemampuan membaca dianggap sebagai kemampuan yang paling sulit untuk dikuasai. Karena dalam membaca, siswa tidak hanya dituntut untuk membaca dengan seksama dan hati-hati tetapi juga dituntut untuk memahami isi dari bacaan tersebut. Untuk memahami suatu bacaan bukanlah hal yang mudah namun membutuhkan rencana atau strategi. Strategi dalam membaca sangatlah penting untuk membantu siswa dalam memahami sebuah teks jadi mereka tidak hanya membaca suatu teks namun juga paham akan isinya. Ada sangat banyak strategi membaca yang dapat digunakan, salah satunya adalah SQ3R. SQ3R adalah sebuah strategi yang tepat untuk digunakan membaca artikel, buku, tabloid, karya nonfiksi, dll. Strategi ini akan memotivasi siswa untuk fokus berkonsentrasi melalui 5 fase yang berbeda. Strategi SQ3R memiliki 5 fase. Setiap fase memiliki kegunaan dan aktifitas yang berbeda untuk membantu siswa dalam memahami isi dari sebuah teks. Dalam fase Survey, siswa melakukan ulasan singkat dengan cara membaca judul, sub judul, gambar, tabel, paragraf kesimpulan, dll. Sebagai tambahan, siswa diminta untuk membuat prediksi tentang teks yang akan dibaca. Fase kedua adalah question. Siswa diminta untuk membuat pertanyaan sesuai dengan isi dari teks (mengubah judul/sub judul menjadi pertanyaan), yang kemudian akan mereka jawab nantinya. Di faseketiga yaitu read, siswa diminta untuk membaca dengan hati-hati dan menemukan topik utama dari teks tersebut. Di fase recite, siswa diminta untuk menjawab pertanyaan yang telah mereka buat dan diminta untuk menceritakan ulang teks yang telah mereka baca menggunakan kata-kata mereka sendiri. Fase terakhir adalah review. Dalam fase ini siswa diminta kembali untuk membaca ulang teks tersebut untuk memperdalam pemahaman mereka. Mereka juga diminta untuk membuat rangkuman teks tersebut untuk membantu dalam mengingat informasi yang terkandung dalam teks. Menggunakan teks news item dalam proses pembelajaran ini merupakan hal yang tepat karena teks news item merupakan salah satu dari banyak karya nonfiksi dan teks tersebut juga digunakan dalam pembelajaran dan juga dipakai dalam pembelajaran di kelas 10 (sepuluh) SMA. Penelitian ini merupakan penelitian descriptive qualitative dan penelitian ini bertujuan untuk mendeskripsikan penggunaan SQ3R sebagai strategi dalam pembelajaran membaca teks news item, mengetahui sejauh mana pemahaman siswa setelah penggunaan SQ3R dan juga respon siswa terhadap penggunaan SQ3R. Instrumen dari penelitian ini, peneliti menggunakan obsevation checklist dengan bantuan field notes, tugas siswa dan questionnaire. Data yang didapat dalam penelitian ini akan disajikan dalam bentuk kalimat. Setelah melakukan observasi, peneliti menemukan fakta bahwa SQ3R sangat membantu siswa dalam memahami teks news item. Hasil dari tugas siswa menunjukkan bahwa kemampuan siswa dalam membaca telah meningkat. Siswa juga setuju bahwa penggunaan SQ3R dalam pembelajaran membaca sangatlah membantu. Peniliti menganjurkan para guru bahasa Inggris untuk menggunakan SQ3R sebagai alternatif srategi dalam kegiatan membaca. Hal ini sangat penting karena pemahaman dalam membaca adalah hal vital. Kata Kunci: SQ3R (Survey, Question, Read, Recite, Review), strategi, pengajaran membaca, teks news item.